Animal corpse degradation enriches antibiotic resistance genes but remains recalcitrant in drinking water microcosm. (March 2022) - Su, Wanghong; Li, Tongtong; Yu, Qiaoling; Feng, Tianshu; Yang, Jiawei; Qu, Jiapeng; Li, Xiangzhen; Li, Huan
Abstract : Serious concerns have been raised regarding resistomes caused by corpse decomposition in the aquatic environment, which has posed threats to the water environment and human health. However, antibiotic resistance genes (ARGs) in large-volume tap water and their temporal stability during corpse decay are poorly explored. Here, high-throughput quantitative polymerase chain reaction (HT-qPCR) and amplicon sequencing were applied to profile ARGs and bacterial communities in experimental and control groups containing 50 L of tap water at 7th, 15th and 100th day during corpse decomposition. Our results suggested that most of the ARGs in experimental group had higher abundance compared with the control group independent of time. Some ARGs' absolute abundance like tetracycline and beta-lactamase was even enriched by 259 – 413, 640-folds during corpse decay. Twelve opportunistic pathogens, especially Burkholderia, Legionella and Halomonas, remarkably increased as decomposition proceeded. Furthermore, network analysis showed that opportunistic pathogens were significantly associated with ARGs. Our results emphasize that corpse decay increases the abundance and diversity of ARGs in large-volume drinking water independent of time while exhibiting temporal persistence of ARGs, thereby uncovering the harmful effects of animal cadavers. Our study also provides valuable suggestions for the risk assessment and management of source water caused by corpse decay. Graphical abstract: Image 1 Highlights: ∙ Corpse decay increases the abundance of ARGs in large-volume drinking water ∙ Most of the ARGs remains relative stable abundance over decomposition time. ∙ Twelve opportunistic pathogens were significantly associated with ARGs. ∙ Treatment, dissolve oxygen (DO) and pH were important factors influencing ARGs' spread.